Cameroon's multidrug-resistant tuberculosis treatment programme jeopardised by cross-border migration. Issue 2 (February 2016) - Matteelli, Alberto; Lönnroth, Knut; Mosca, Davide; Getahun, Haileyesus; Centis, Rosella; D'Ambrosio, Lia; Jaramillo, Ernesto; Migliori, Giovanni Battista; Raviglione, Mario C.
We read with interest the correspondence from J. Noeske and colleagues on the potential effect of cross-border migration on the multidrug-resistant tuberculosis (MDR-TB) treatment programme in Cameroon, elicited by our article on the framework for TB elimination in low TB incidence countries [1]. The manuscript highlights some of the consequences of cross-border migration for caring for people with TB and ending this epidemic, as well as relevant issues on clinical and public health management of MDR-TB in Cameroon. Cross-border migration: migrant and native populations' health cannot be ignored by national TB programmes http://ow.ly/U7TO4